(untitled) - Bey, Russell F. (Australia, 2001)
working in a microbiology laboratory presents a unique opprtunity to learn some basic principles on the safe handling of fluids and other materials that contain microorganisms. Through a series of experiments you will learn aseptic techniques that will allow you to effectively and safely work with microorganisms...
Keywords: bacteriology,microbiology; laboratory manuals,laboratory manuals